AKSIN “ AKSESORIS RESIN " - Eli Elpan Sinaga (Jurnal Pengabdian Kepada Masyarakat Babakti, 2022)
Abstract (90) words This entrepreneurship is one of the student creativity programs, in this study we created an entrepreneurial resin accessories business. This resin accessory or abbreviated as axin is a business product made from liquid resin and its supports. This method of entrepreneurship uses resin manufacturing and marketing methods. The result of this entrepreneurial activity is that we have succeeded in making resin with makeshift tools and materials, but still needs a lot of development. more for the future. Aksin business is a business that makes and sells accessories made from liquid resin and several supporting motifs to increase the attractiveness of the product.